Exploring the Influence of Materialism and Tourism Brand Attachment on Compulsive Travel Purchases Among Young Consumers in Post-COVID-19 Indonesia - Praharjo, Ardik Angga; Parwati, Kardina Yudha; Rofida N, Khusnul (MEC-J (Management and Economics Journal), 2025)
This study aims to examine the influence of materialism and tourism brand attachment on compulsive buying for travel among generations Y and Z in Indonesia. Additionally, it investigates the antecedents of materialism and compulsive buying, including SNS advertisements, celebrity endorsements, and ideal self-congruence. An explanatory research design with a quantitative approach was employed, using a survey with structured questionnaires to collect primary data. The population consisted of all Indonesian generations Y and Z, and purposive non-probability sampling was applied, targeting respondents born in 1981 or later and active users of social media, to ensure relevance to SNS-related variables. A total of 200 respondents participated in the study, consisting of individuals from Generation Z and Generation Y. Data were analysed using PLS-SEM. The results indicate that materialism and tourism brand attachment positively and significantly influence compulsive buying, while SNS advertisements and celebrity endorsements significantly affect materialism. Moreover, ideal self-congruence significantly influences tourism brand attachment. These findings highlight the roles of psychological and marketing factors in shaping impulsive travel behaviours and provide theoretical and managerial implications for tourism marketing strategies targeting young consumers.